Successful cochlear implantation in a patient with Epstein syndrome during long-term follow-up. Issue 2 (April 2022) - Mori, Anjin; Takeda, Hidehiko; Kobayashi, Marina; Misawa, Takeru; Watanabe, Ryoko; Abe, Satoko; Kumakawa, Kozo; Nishio, Shinya; Usami, Shinichi; Yamasoba, Tatsuya
Abstract: Epstein syndrome is a rare disease characterized by macrothrombocytopenia, nephritis and progressive sensorineural hearing loss (SNHL). This syndrome is presently recognized as an autosomal dominant disease caused by mutations of non-muscle myosin heavy chain 9 ( MYH9 ). Little information is available about the progress of SNHL, the efficacy of cochlear implants (CI) or the perioperative management of thrombocytopenia in patients with Epstein syndrome. We herein report a case of a patient with Epstein syndrome with the MYH9 :c.2105G>A:p.R702H variant who underwent cochlear implantation after 27 years of follow-up for her progressive SNHL. The deterioration rates of hearing were 3.48 dB/year on the right ear and 2.46 dB/year on the left ear. The patient derived benefits from CI and had a speech recognition test result (for sentences) of 93% at 6-months postoperatively. Thrombocytopenia was successfully managed without any bleeding complications by using eltrombopag, an oral thrombopoietic agent, making transfusion of platelets unnecessary. The accurate diagnosis of Epstein syndrome was made only after long-term follow-up as the thrombocytopenia was initially diagnosed as idiopathic thrombocytopenic purpura. This case report highlights the perioperative management of thrombocytopenia, the progress of SNHL and the potential pitfalls of diagnosis.